Competitive Advantages Based on Market Orientation and Innovation - Yulianingsih; Palahudin Palahudin; Masnur Mukmin (Universitas Djuanda, 2021)
The research objective was to determine the effect of market orientation and innovation on competitive advantage. This research is field research on bag artisans in Bojong Rangkas Village, Ciampea District, Bogor Regency. The population of the study was 150 bag craftsmen using the Slovin formula and obtained a sample of 60 respondents. Distribution of questionnaires using an accidental sampling technique. Data analysis carried out; (1) test the research instruments in the form of validity and reliability tests; (2) classic assumption tests in the form of normality, multicollinearity, and heteroscedasticity tests. After the data fulfills all the classical assumptions, then multiple linear regression analysis, determination test, t-test, and F test are carried out. The research findings show that market orientation and innovation have a positive effect on competitive advantage in the bag craftsmen of Bojong Rangkas village, Ciampea district. The managerial implication of the research results is to increase the competitive advantage of the Bojong Rangkas bag artisans; attention to market orientation and innovation are important things that must be done. As for how to improve market orientation and innovation, the bag craftsmen must be oriented towards consumer desire and satisfaction.